Pediatric Acute Lymphoblastic Leukemia Patients Exhibit Distinctive Alterations in the Gut Microbiota - Liu, Xiaoming; Zou, Yao; Ruan, Min; Chang, Lixian; Chen, Xiaojuan; Wang, Shuchun; Yang, Wenyu; Zhang, Li; Guo, Ye; Chen, Yumei; Zhang, Yingchi; He, Hongrui; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Previous studies have shown that gut microbiota can affect human immune system in many ways. Our aim was to investigate quantitative differences in faecal bacterial compositions of childhood acute lymphoblastic leukemia (ALL) patients compared to those of healthy children, so as to identify individual bacterial species that are related to the etiology of ALL. We recruited 81 subjects, including 58 patients with ALL and 23 healthy controls. Fecal samples were collected and examined by 16S rRNA quantitative arrays and bioinformatics analysis. Both Principal Coordinates Analysis (PCoA) and Non-metric Multidimensional scaling (NMDS) demonstrated that the microbial composition of ALL patients deviated from the tight cluster of healthy controls. Multiple bacterial species exhibited significant changes (e.g., Roseburia faecis, Edwardsiella tarda and Fusobacterium naviforme) in the ALL samples. Some of the differentially abundant taxa were correlated with the level of interleukin-10. The ALL cases could be efficiently distinguished from healthy controls by the random forest model based on differential species (area under ROC curve = 0.843). Taken together, the composition of gut microbiota differed from healthy controls to pediatric ALL patients. Our study identified a series of ALL-related species in the gut microbiota, providing a new direction for future studies aiming to understand the host-gut microbiota interplay in ALL pathogenesis.